2016
DOI: 10.1080/15384101.2016.1160976
|View full text |Cite
|
Sign up to set email alerts
|

CDKIs p18INK4cand p57Kip2are involved in quiescence of CML leukemic stem cells after treatment with TKI

Abstract: Chronic Myeloid Leukemia (CML) is sustained by a small population of cells with stem cell characteristics known as Leukemic Stem Cells that are positive to BCR-ABL fusion protein, involved with several abnormalities in cell proliferation, expansion, apoptosis and cell cycle regulation. Current treatment options for CML involve the use of Tirosine Kinase Inhibitor (Imatinib, Nilotinib and Dasatinib), that efficiently reduce proliferation proliferative cells but do not kill non proliferating CML primitive cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…36 TKIs, which directly target the activation of Bcr-Abl, inhibit proliferation of bulk CML cells; however, a fraction of LSC has been shown to enter quiescence and avoid apoptosis. 15 Here, we found that a fraction of CML cells is able to survive PTL and DMAPT the arrest on cell cycle to be reversed by NAC pre-treatment; however, to our surprise we found that while cells were consistently rescued from cell death with NAC pre-treatment, they readily suffered a cell cycle arrest that could not be explained by ROS induction.…”
Section: Cell Cycle Arrest By Ptl and Dmapt Is Related To Cyclin Domentioning
confidence: 47%
See 2 more Smart Citations
“…36 TKIs, which directly target the activation of Bcr-Abl, inhibit proliferation of bulk CML cells; however, a fraction of LSC has been shown to enter quiescence and avoid apoptosis. 15 Here, we found that a fraction of CML cells is able to survive PTL and DMAPT the arrest on cell cycle to be reversed by NAC pre-treatment; however, to our surprise we found that while cells were consistently rescued from cell death with NAC pre-treatment, they readily suffered a cell cycle arrest that could not be explained by ROS induction.…”
Section: Cell Cycle Arrest By Ptl and Dmapt Is Related To Cyclin Domentioning
confidence: 47%
“…Although TKI treatments are very effective targeting Bcr‐Abl activation, the quiescent leukaemic pool has been reported as not sensitive to this inhibition 27. Recently, our group reported that the G0/G1 phase fraction increases in CML cells after being treated with TKIs, and that this is dependent on nuclear localization of CDK inhibitors p21 and p18 15. NF‐κB has also been reported as a regulator of cell cycle, and it is therefore relevant to all new therapeutic strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quiescent cancer cells complicate diagnosis, target therapeutic drugs (TKIs) interventions, chemotherapy and are generally difficult to tackle. The current treatment regimen that involves the use of tyrosine Kinase Inhibitors for rapidly dividing cells do not kill quiescent cells that contribute to cancer relapse [121].…”
Section: Tyrosine Kinase Receptors/tyrosine Kinase Inhibitors and Quimentioning
confidence: 99%
“…Indeed, both normal and CML hematopoietic stem cells (HSCs) are comprised within a cell population expressing the CD34 antigen, and lacking the expression of CD38 and any lineage‐specific antigen; so that they are referred to as lineage‐negative (Lin − ) cells. The vast majority of normal and leukemic HSCs are quiescent, thus, leukemic HSCs (leukemic stem cells or LSCs) are insensitive to most chemotherapeutic agents, including tyrosine kinase inhibitors, such as IM . Furthermore, both normal HSCs and LSCs reside in specific niches within the bone marrow; such niches play important roles in stem cell function and recent evidence suggests that they contribute to leukemic cell resistance to drugs by protecting them from the action of antineoplastic agents .…”
Section: Introductionmentioning
confidence: 99%